Capacity Enhancement of Hepatitis C Virus Treatment through Integrated, Community-Based Care. (2008) - Hill, Warren D; Butt, Gail; Alvarez, Maria; Krajden, Mel
Abstract : BACKGROUND: An estimated 250, 000 Canadians are infected with the hepatitis C virus (HCV). The present study describes a cohort of individuals with HCV referred to community-based, integrated prevention and care projects developed in British Columbia. Treatment outcomes are reported for a subset of individuals undergoing antiviral therapy at four project sites. METHODS: Four demonstration projects based on a public health nurse and physician partnership were established in rural and small urban centres in British Columbia. Comprehensive medical assessments determined whether individuals received treatment, or counselling and education. Outcomes of the treatment group were compared with published randomized controlled trials. Client demographics were mapped using geographical information systems applications. RESULTS: A total of 1795 individuals were referred to the clinics for medical assessment between Septmber 2001 and December 2005. After assessment, 26% were eligible for therapy, while 74% received counselling and education. Wait times decreased annually, with one-half of all referrals assessed within 30 days. Combination antiviral therapy was initiated in 363 clients with interferon plus ribavirin (n=36) or pegylated interferon plus ribavirin (n=327). Treatment outcomes were available for 205 individuals. The overall rate of sustained virological response was 61% (126 of 205 individuals). The number of individuals assessed at each site represented, on average, 20% of the total cumulative reported HCV cases in the catchment areas. DISCUSSION: The study findings illustrate how a public health nurse and physician partnership can service a population with complex medical needs while simultaneously increasing local capacity. Treatment outcomes were comparable with published clinical trials.